Pengaruh Semangat Kerja Dan Disiplin Kerja Terhadap Kinerja Guru Di Smp Pawyatan Daha 1 - Mohammad Iqbal Abidin; Diana Ambarwati; Zaenul Muttaqien (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
This research aims to determine how significant the effect of morale and work discipline on teacher performance. This type of research uses a quantitative approach. The research sample was Pawyatan Daha 1 Middle School teachers with a total of 34 respondents. This study uses a saturated sample technique. The data collection technique uses a questionnaire that has been tested for validity and reliability first. This research data analysis technique uses multiple linear regression.